(untitled) (European Journal of Marketing and Economics, 2020)
The COVID-19 pandemic involves the major risk of a severe recession, and of the economic, financial, social, educational crises, which will affect the entire EU economy, with consequences for citizens, businesses, jobs, and households. In order to guarantee the continued availability of sufficient liquidity on the market, to counteract the damage caused to healthy enterprises and to maintain the continuity of economic activity during the epidemic and after the end of the COVID-19 pandemic, it is necessary to develop a plan of measures and solutions. supporting the European economy, both through direct measures of state aid, as well as through measures to support/develop/innovate the business environment through the EU funding programs allocated at the level of the Member States both in the period 2014-2020, but more elected 2021-2027, the effects of the current crisis being both short term, but especially in the medium and long term. Among the objectives pursued we propose: identification and proposal of state aid measures to support the economy in the context of the current epidemic of COVID-19 through close coordination at European level of the aid measures; estimating the impact of temporary state aid measures on the European economy through the intervention of the European Commission; and ways to attract European funds for the business environment through the European Union funding programs existing in the budget for the period 2014-2020, but especially for the period 2021-2027.